Convergence as a new paradigm of engineering and reengineering in construction - S. B. Sborshchikov; N. V. Lazareva (Vestnik MGSU)
Introduction. Any development can be affected by two phenomena of convergence and divergence. Convergence is the process of convergence of the levels of development of systems (economic, social, anthropotechnical) over time, and the opposite process is called divergence. These phenomena are mainly caused by the processes of globalization and scientific and technological progress. The classification of types of convergence is provided and their definitions are given. The practical implementation of the concept of convergence is associated with theoretical constructions in relation to engineering and reengineering, which in turn determine the necessity of the formation of a new organizational and economic mechanism for investment and construction activities, which may be based on the use of dissipative organizational structures. The paper defines such structures and identifies their main properties and limitations in implementation.Materials and methods. The study used the provisions of a systematic approach, structural and functional analysis of investment and construction management, methodology of logistics of regulatory influences, as well as methods of investment design, strategic, operational management in the context of the development of the theory of life cycle management of capital construction facilities.Results. The analysis of the manifestation of convergence in the investment and construction sector is carried out, including its causes, classification and terminological identification of types of convergence are given, the influence of convergence on the reengineering of business processes and organizational structure in construction is established, and on this basis a theoretical justification is given for the use of dissipative organizational structures to ensure sustainable development.Conclusions. The phenomenon of convergence largely determines such type of activity as reengineering, which is aimed at increasing efficiency through transformation and rational construction of management processes, as well as organizational structures in the presence of dissipation of regulatory influences.